Strategi Komunikasi Wanita dalam Film Barbie - Vivi Novalia Sitinjak; Grace Cya Aprilia S. Meliala; Riska Wati Sihombing; Maria Yosepine Simamora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study, conducted in a sociolinguistic setting, looks into the communication strategies utilized by female characters in the animated film